PEMEDIASIAN PERSEPSI MANFAAT PADA KUALITAS KONTEN DAN DESAIN LEARNING MANAGEMENT SYSTEM TERHADAP INTENSI BELAJAR BERKELANJUTAN - Krismi Sienatra; Romauli Nainggolan; Deandra Vidyanata; Yuli Kartika Dewi; I Gusti Bagus Yosia (STEKOM PRESS, 2021)
The covid-19 pandemic causes learning to be carried out boldly with the concept of e-learning. The learning providers must design their learning content on a cloud-based learning management system (LMS). The preparation of material content and learning design in the learning management system must be well organized so that users feel the benefits and will continue to use the learning management system as a learning tool. This paper aims to observe effect of design quality and content quality on the intensity of continuous learning by perceived usefulness as a mediating variable. The sample in this study were students who used the LMS to access learning material content that had been compiled completely and completely. The data analysis tool used was partial least square (PLS). The results showed that the quality content had no effect on continuance learning intentions and design quality had an effect on learning intentions with perceived usefulness.